Remoção de nutrientes e contaminantes emergentes em um sistema de tratamento de efluente hospitalar composto de um reator anóxico-lodos ativados de aeração prolongada - Campos, Roger Francisco Ferreira de (2024)
The presence of micropollutants in the environment is a significant environmental indicator, often linked to conventional biological treatment systems. These systems, generally, are not specifically designed to handle emerging compounds, highlighting the need for in-depth studies on the interaction and removal of these compounds in various treatment methods. While oxic activated sludge systems (O-Activated Sludge) are widely used for wastewater treatment, studies related to anoxic-oxic systems (A/O–Activated Sludge) remain limited in the context of removing emerging compounds. The present work aims to analyze the presence and removal of emerging compounds in a full-scale hospital wastewater treatment system using an anoxic-oxic reactor. To develop the study, an analysis of removal efficiency during different seasonal periods was conducted, along with specific collections to analyze environmental correlation using physicochemical parameters and micropollutants. The seasonal interaction study was conducted with a Hydraulic Retention Time (HRT) of 24 hours, while the environmental correlation study was carried out with an HRT of 36.45 hours, with samples taken at 2-hour intervals. In the seasonal study, 5 emerging compounds from the antibiotic class, 5 compounds from the hormone class, 6 compounds from the antibiotic class, and 1 compound from each of the following classes: corticosteroid, stimulant, diuretic, and antilipemic were evaluated. In the environmental correlation study, comprising the fifth collection, the analysis of 3 natural hormones and 1 stimulant was performed, consisting of Progesterone (PRO), estradiol (E2), estrone (E1) and caffeine (CF). The study showed good efficiency throughout the seasonal periods. Temperature proved to be a limiting factor for the treatment via A/O–Activated Sludge, since the efficiency was greater in warmer seasons than in colder seasons. In the autumn and winter seasons, denitrification and nitrification were reduced in the A/O–Activated Sludge system. Throughout the different seasonal periods, 19 emerging compounds were detected, with Ibuprofen (IBU) presenting the highest concentration in the raw effluent (9405.32 µg L-1) and furosemide (FR) in the treated effluent (546.62 µg L-1). The study indicated that the HRT period is a limiting factor in the removal efficiency of emerging compounds. In the environmental correlation study, removal efficiencies of 21.22% for PRO, 100% for E2, 80.37% for E1 and 98.43% for CF were observed. Further studies are needed to deepen the understanding of the treatment mechanisms of anoxic-oxic systems, aiming to optimize their efficiency and effectiveness in removing these compounds.